Transpressional motions along the Cordillera Occidental - coastal belt boundary since the Late Cretaceous (southern Peru, 16°S) - Romero Fernández, Darwin (2002)
The study area is located in southern Peru NW of the city of Arequipa (16° S) at the boundary between the Cordillera Occidental and coastal belt. Previous studies sustain that exists in the area a large overthrust, named the Cincha-L1uta overthrust (Vicente et aI., 1979). Recent studies realized in the Huambo (32-r) (Romero & Ticona, 2002; Cruz, 2002) and Aplao (33-r) sheets permit to observe NE-vergent thrusts (areas of Andamayo and Ayo). To the SW, however, in the Majes valley (areas of Aplao and Santa Elena), SW-vergent thrusts are observed. In the central areas of Andamayo and Aplao, faults are subvertical and display evidence of senestral motions, affecting rocks of the Coastal. This work presents the results of an integrated regional study that permits to better understand which tectonic, sedimentary and magmatic processes occurred in the area. We interpret the mentioned fault system as a large flower-structure, which resulted from transpressional motions.